Boundaries [videorecording (DVD)] - Feste, Shana, 1976-; Farmiga, Vera; Plummer, Christopher; MacDougall, Lewis, 2002- (Sony Pictures Classics, 2018)
Laura and her son Henry are forced to drive her estranged, pot-dealing, carefree father Jack across country after being kicked out of a nursing home.